Host-Based Intrusion Detection System (HIDS) - Mohamad Nazim, Jambli (Universiti Malaysia Sarawak, (UNIMAS), 2001)
Host-based Intrusion Detection System (HIDS) is another alternative approach of security measures taken by computer experts widely since the implementation of Access Control List (ACL) in protecting the privacy of a network. Yet this Firewall step is taking its leap by storm with the collaboration of various types of IDS. Another RIDS can work on top of another IDS with the Firewall co-exist in the Internet as well. The collaboration of HIDS with another form of IDS and the firewall as such would provide a stronger security. This is to ensure that prevention and detection role covers the security management effectively and widely. The aim of this project is to ensure that more security features can be added by expanding the criteria that what a Firewall can hold. This project describes a prototype Host-based Intrusion Detection System (HIDS) based on LINUX platform. The system supports a number of fake components such as port binding, finger, telnet and ftp. These fake components are used to observe the intruder's activities inside the false environment called a jail